Circadian Clocks in Mouse and Human CD4+ T Cells - Bollinger, Thomas; Leutz, Anton; Leliavski, Alexei; Skrum, Ludmila; Kovac, Judit; Bonacina, Luigi; Benedict, Christian; Lange, Tanja; Westermann, Jürgen; Oster, Henrik; Solbach, Werner (PloS one, 2011)
Though it has been shown that immunological functions of CD4+ T cells are time of day-dependent, the underlying molecular mechanisms remain largely obscure. To address the question whether T cells themselves harbor a functional clock driving circadian rhythms of immune function, we analyzed clock gene expression by qPCR in unstimulated CD4+ T cells and immune responses of PMA/ionomycin stimulated CD4+ T cells by FACS analysis purified from blood of healthy subjects at different time points throughout the day. Molecular clock as well as immune function was further analyzed in unstimulated T cells which were cultured in serum-free medium with circadian clock reporter systems. We found robust rhythms of clock gene expression as well as, after stimulation, IL-2, IL-4, IFN-γ production and CD40L expression in freshly isolated CD4+ T cells. Further analysis of IFN-γ and CD40L in cultivated T cells revealed that these parameters remain rhythmic in vitro. Moreover, circadian luciferase reporter activity in CD4+ T cells and in thymic sections from PER2::LUCIFERASE reporter mice suggest that endogenous T cell clock rhythms are self-sustained under constant culture conditions. Microarray analysis of stimulated CD4+ T cell cultures revealed regulation of the NF-κB pathway as a candidate mechanism mediating circadian immune responses. Collectively, these data demonstrate for the first time that CD4+ T cell responses are regulated by an intrinsic cellular circadian oscillator capable of driving rhythmic CD4+ T cell immune responses.